2013
DOI: 10.1016/j.jnoncrysol.2013.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Silica phase formed by sol–gel reaction in the nano- and micro-pores of a polymer hydrogel

Abstract: ElsevierPlazas Bonilla, CE.; Gómez-Tejedor, JA.; Perilla, JE.; Gómez Ribelles, JL. (2013). Silica phase formed by sol-gel reaction in the nano-and micro-pores of a polymer hydrogel. Journal of Non-Crystalline Solids. 379:12-20. doi:10.1016/j.jnoncrysol.2013. Corresponding author José L. Gómez Ribelles .E-mail address: jlgomez@ter.upv.es AbstractHybrid composites consisting in a hydrogel matrix with silica micro-and nano-particles reinforcement were produced and characterized. The strategy proposed in this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In previous studies we have shown that the silica coating of the pore walls of polymeric porous membranes through in situ sol–gel yields hybrid materials with interesting mechanical and water sorption and permeation properties . Chitosan–silica blends were also tested as fillers of polymer membranes showing mechanical reinforcement and enabling the tuning of mechanical properties by varying the ratio chitosan–silica in the coating .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies we have shown that the silica coating of the pore walls of polymeric porous membranes through in situ sol–gel yields hybrid materials with interesting mechanical and water sorption and permeation properties . Chitosan–silica blends were also tested as fillers of polymer membranes showing mechanical reinforcement and enabling the tuning of mechanical properties by varying the ratio chitosan–silica in the coating .…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, we have proposed a novel strategy for the preparation of hybrid porous materials performing sol–gel reactions using silica precursors inside the pores of polymeric high‐interconnected porous membranes, obtaining a homogeneous thin layer upon the pore walls of the membrane . The silica layer deposited highly reinforced the polymer, for that reason we also produced a tuneable reinforced hybrid material filling the pores of the membrane with a blend of chitosan–silica network .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in previous papers that sol‐gel reaction taking place while the sol is confined in the pores of a polymer could yield a variety of silica phase micro or nanostructures depending on the capacity of the precursor to penetrate into the polymer matrix and on the catalyst used. Thus, sol‐gel reaction performed into a microporous membrane of poly(hydroxyethyl acrylate) yields a non‐porous composite with a silica phase consisting in interconnected nano and micro‐domains because silica is in part formed into the nanopores of the hydrogel and in part in the macropores of the membrane, and silica interconnectivity collapses any remaining empty spaces. When silica is formed into the pores of a polycaprolactone membrane the polymer is not swollen by the precursor solution and silica is formed as a coating of the pore walls if sol‐gel reaction is performed at low pH or as dispersed microparticles loosely adhered to each other or the pore walls if performed at high pH …”
Section: Resultsmentioning
confidence: 99%
“…In this type of measurements where a controlled time‐dependent compression force is applied the obtained force‐penetration curves allow the evaluation of the material Compliance . Following the analysis of Hayes with the procedure described in ref the creep compliance of a sample with thickness h intended by a stiff flat‐ended cylindrical indenter with radius α could be evaluated from the load ( F ) ‐ penetration ( w ) curve through the Eq. (6): J(t)=4ak(1ν)dFdtdwdt where k is a non‐dimensional parameter which depends on the ratio, α/h , and the Poisson coefficient of the material, ν .…”
Section: Resultsmentioning
confidence: 99%